Green economy indicators as a method of monitoring development in the economic, social and environmental dimensions - Daniek, Kamila (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The economic crisis of 2008 became a turning point in international debates during which the issue related to the need to transform the current economic model was raised and discussed. The idea of the green economy, based on the concept of sustainable development, became the focal point of the new strategy. One of the issues related to the development of the green economy was how it could be monitored at both the local and international levels. The aim of the article is a comparative assessment of selected sets of indicators for measuring the transformations towards the green economy in terms of four dimensions: economic, social, environmental and political. The research method is a critical analysis of selected research describing how to measure the green economy. The article presents international sets of indicators proposed by such organizations as the OECD and UNEP, as well as composite indicators such as the Global Green Economy Index and the Green Economy Progress. The article also highlights the results of Polish researchers and research institutions, which include the Green Economy Index constructed by Bożena Ryszawska and the Green Economy Indicators proposed by Central Statistical Office in Poland. Selected indicators were also analysed and compared in the economic, social, environmental and political dimensions. An attempt was made to formulate their synthetic characteristics. This study is primarily the result of exploring foreign literature complemented with Author’s thoughts and conclusions. Discussions on the theme of the green economy are centred around the effects of implementing it. This is why there is a need to conduct research into how to determine progress in greening current economies across countries in a manner as close to the current situation as possible.

Kryzys gospodarczy z 2008 r. stał się punktem zwrotnym w międzynarodowych debatach, w których poruszono i omówiono kwestię konieczności transformacji obecnego modelu gospodarczego. Idea zielonej gospodarki, oparta na koncepcji zrównoważonego rozwoju, stała się centralnym punktem nowej strategii. Jeden z obszarów problematycznych związanych z rozwojem zielonej gospodarki to sposób jej monitorowania, zarówno na poziomie lokalnym, jak i międzynarodowym. Celem artykułu jest porównanie wybranych zestawów wskaźników do mierzenia transformacji w stronę zielonej gospodarki. Metoda badawcza to krytyczna analiza wybranych badań opisujących sposoby mierzenia zielonej gospodarki. W artykule przedstawione zostały zarówno międzynarodowe zestawy wskaźników zaproponowane przez takie organizacje, jak OECD i UNEP, jak również wskaźniki złożone takie jak Global Green Economy Index oraz Green Economy Progress. Oprócz przeglądu zestawów międzynarodowych, w artykule wyróżniono rezultaty wysiłków polskich badaczy i instytucji badawczych, do których należy Indeks Zielonej Gospodarki skonstruowany przez Bożenę Ryszawską oraz Wskaźniki Zielonej Gospodarki zaproponowane przez GUS. Dokonano również analizy wybranych wskaźników i porównano je ze względu na wymiar ekonomiczny, społeczny, środowiskowy oraz polityczny, a także podjęto próbę syntetycznego sformułowania ich cech charakterystycznych. Badanie jest efektem przede wszystkim eksploracji zagranicznej literatury, uzupełnione o własne przemyślenia i wnioski. Dyskusje nad tematyką zielonej gospodarki toczą się wokół efektów, które niesie ze sobą jej konsekwentne wdrażanie. Stąd też rośnie konieczność prowadzenia badań nad tym, aby w sposób jak najbardziej zbliżony do stanu faktycznego móc określić progres zazieleniania się obecnych gospodarek wśród wszystkich państw.
Keywords: green economy; green economy indicators; green economy measurement; zielona gospodarka; wskaźniki zielonej gospodarki; pomiar zielonej gospodarki